A GLP‐1/GLP‐2 receptor dual agonist to treat NASH: Targeting the gut‐liver axis and microbiome. Issue 6 (18th December 2021) - Kim, Eun Ran; Park, Jeong Su; Kim, Jin Hee; Oh, Ji Young; Oh, In Jeong; Choi, Da Hyun; Lee, Yu seol; Park, I. Seul; Kim, SeungWon; Lee, Da Hyun; Cheon, Jae Hee; Bae, Jin‐Woo; et al.
Abstract: Background and Aims: Currently there is no Food and Drug Administration–approved drug to treat NAFLD and NASH, the rates of which are increasing worldwide. Although NAFLD/NASH are highly complex and heterogeneous conditions, most pharmacotherapy pipelines focus on a single mechanistic target. Considering the importance of the gut‐liver axis in their pathogenesis, we investigated the therapeutic effect of a long‐acting dual agonist of glucagon‐like peptide (GLP)‐1 and GLP‐2 receptors in mice with NAFLD/NASH. Approach and Results: C57BL/6J mice were fed a choline‐deficient high‐fat diet/high fructose and sucrose solution. After 16 weeks, mice were randomly allocated to receive vehicle, GLP1‐Fc, GLP2‐Fc, or GLP1/2‐Fc fusion (GLP1/2‐Fc) subcutaneously every 2 days for 4 weeks. Body weight was monitored, insulin/glucose tolerance tests were performed, feces were collected, and microbiome profiles were analyzed. Immobilized cell systems were used to evaluate direct peptide effect. Immunohistochemistry, quantitative PCR, immunoblot analysis, tunnel assay, and biochemical assays were performed to assess drug effects on inflammation, hepatic fibrosis, cell death, and intestinal structures. The mice had well‐developed NASH phenotypes. GLP1/2‐Fc reduced body weight, glucose levels, hepatic triglyceride levels, and cellular apoptosis. It improved liver fibrosis, insulin sensitivity, and intestinal tight junctions, and increased microvillus height, crypt depth, and goblet cells of intestine compared with a vehicle group. Similar effects of GLP1/2‐Fc were found in in vitro cell systems. GLP1/2‐Fc also changed microbiome profiles. We applied fecal microbiota transplantation (FMT) gain further insight into the mechanism of GLP1/2‐Fc–mediated protection. We confirmed that FMT exerted an additive effect on GLP1‐Fc group, including the body weight change, liver weight, hepatic fat accumulation, inflammation, and hepatic fibrosis. Conclusions: A long‐acting dual agonist of GLP‐1 and GLP‐2 receptors is a promising therapeutic strategy to treat NAFLD/NASH.